Simultaneous Quantification of Chloramphenicol, Thiamphenicol, Florfenicol, and Florfenicol Amine in Animal and Aquaculture Products Using Liquid Chromatography-Tandem Mass Spectrometry - Jung, Hae-Ni; Park, Da-Hee; Choi, Yeon-Jae; Kang, Se-Hyeong; Cho, Hee-Jung; Choi, Jeong-Min; Shim, Jae-Han; Zaky, Ahmed A.; Abd El-Aty, A. M.; Shin, Ho-Chul (Frontiers in Nutrition, 2022)
The accumulation of antimicrobial residues in edible animal products and aquaculture products could pose health concerns to unsuspecting consumers. Hence, this study aimed to develop a validated method for simultaneous quantification of chloramphenicol (CAP), thiamphenicol (TAP), florfenicol (FF), and florfenicol amine (FFA) in beef, pork, chicken, shrimp, eel, and flatfish using a quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction method coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Primary-secondary amine (PSA) and MgSO4 were used for sample purification. The analytes were separated on a reversed-phase analytical column. The coefficients of determination for the linear matrix-matched calibration curves were ≥ 0.9941. Recovery rates ranged between 64.26% and 116.51% for the four analytes with relative standard deviations (RSDs) ≤ 18.05%. The calculated limits of detection (LODs) and limits of quantification (LOQs) were 0.005–3.1 and 0.02–10.4 μg/kg, respectively. The developed method was successfully applied for monitoring samples obtained from local markets in Seoul, Republic of Korea. The target residues were not detected in any tested matrix. The designed method was versatile, sensitive, and proved suitable for quantifying residues in animal-derived products.